Leadership and spirit breathing new vitality and energy into individuals and organizations - Moxley, Russ S. 1944- (Jossey-Bass Publishers, 1999)
Leadership and Spirit gives all of us the perspective and guidance we need to invest ourselves, our fellow workers, and our entire organizations with an essential sense of purpose, commitment, and fulfillment." "Moxley explains what spirit is and shows why leadership and spirit must be woven together. He analyzes prevalent leadership practices and demonstrates how many of those practices cause spirit to wither and wane. He focuses on the skills and behaviors that give voice to our true selves and increase our capacity to engage in the activity of leadership. And he demonstrates how partnerships serve to create a totally engaged workforce, one that brings the whole person - mental, emotional, physical, and spiritual - to work.